One hand pass training model in basketball games for 13-15 years - Iman Sulaiman; Muhammad Anggana Sulaiman; Karisdha Pradityana (Program Pascasarjana Universitas Negeri Jakarta, 2022)
This study aims to produce an innovative one-handed passing training model in basketball games for beginners that can provide benefits for basketball coaches to convey these varied training models and can help athletes to understand and achieve the expected training results to play basketball well This research method uses research and development (Research & Development). The time required for this research refers to the research and development of the Borg and Gall development model which takes 4 months. The subjects of this study were adolescent athletes aged 13-15 years, The Hawk Basketball team with a total of 60 basketball athletes.